Multi-Pollutant Point-Nonpoint Trading with Participation Decisions: The Role of Transaction Costs - Carson Reeling; Richard D. Horan; Cloé Garnache (Center for Economic Studies and ifo Institute (CESifo), 2018)
High transaction costs and thin participation plague water quality trading and prevent markets from delivering expected efficiency gains. Point sources generate a single pollutant, while nonpoint sources generate multiple, complementary pollutants. We develop a dynamic search model of point-nonpoint trading that includes transactions costs. These costs affect participation decisions and generate strategic complementarities with multiple large or small market participation levels equilibria. Integrated markets—with trading across pollutants—lead to lower transactions costs for both sources and a larger basin of attraction around the full-participation equilibrium, and thus may improve pollution trading efficiency relative to distinct markets.
Keywords: D47; Q53; Q58; 330; credit stacking; multi-pollutant trading; participation; strategic complementarities; transactions costs